Phenotypic and genetic evaluation of production efficiency and life time milk production attributes in Murrah buffaloes - KAMALDEEP, KAMALDEEP; YADAV, A S; DHAKA, S S; MAGOTRA, ANKIT; MALIK, ANIKA; KUMAR, VIJAY (The Indian Journal of Animal Sciences, 2016)
The data of 344 Murrah buffaloes maintained at the university over a period of 20 years from 1993 to 2012 were analysed. From these results, in view of higher heritability estimated for milk yield/day of first calving interval selection on basis of these traits would result in higher genetic improvement in first lactation milk. High genetic and phenotypic correlations of MYFCI with other production efficiency traits also substantiate that, this can be used as a selection criterion. Therefore, selection based on MYFCI would result in improvement in desirable direction through positive correlated response in all the traits under study.